Inaugural edu-action journey with cooperative behavior (Ta’awun) of mKitchen® students in free food for the needy - Ahmad Dahlan, Abdul Rahman; Alias, Majdan; Ibrahim, Jamaludin; Ahmad H.Osman, Rahmah; Mhd. Sarif, Suhaimi; Jaapar, Ghazali; Man, Saupi; Abdul Razak, Dzuljastri; Mohamad Ali, Noor Azian; Abdul Aziz, Normaziah; Mohamadali, Noor Azizah; Mahri, Nurhafizah; et al. (Meso Publishing, 2021)
This book narrates the inaugural edu-action journey with cooperative behaviour (ta’awun) in free food for the needy people at IIUM mKitchen® with Sri Mutiara Teguh Enterprise (cafeteria vendor at Mahallah Aminah IIUM Gombak). The main objective of the project is to transform Mahallah kitchen as a platform to provide free food, to up skill in food-preneurship, to create new employment opportunities, to give empowerment and to nurture entrepreneurship (3Es) among students. Ta’awun refers to cooperative behaviour among the participants, the sponsors, and the beneficiaries in initiating, planning, sponsoring, executing and evaluating the mKitchen® project at Sri Mutiara Teguh Enterprise, Mahallah Aminah. The journey officially started on 1 July 2021 with various student development entities at IIUM. After providing a 4-day online training on business model and plan, financial modelling, and digital marketing, the steering committee has decided to provide the real experience to the students. In conjunction with Malaysia Day on 16 September 2021, the students proposed for cooking and distributing free food to the needy as part of the first proof-of-concept for mKitchen students with the “Keluarga Malaysia” spirit. Nevertheless, the project has to adhere to movement restriction by the authority to prevent the spread of coronavirus disease (COVID-19). The second proof-of-concept is cooking food based on mKitchen students’ business plan.